Perbandingan Hasil Belajar Siswa Dengan Model Pembelajaran Daring dan Luring Pada Mata Pelajaran IPA Tema 1 Subtema 1 PB 6 di Kelas 5 SDN 24 Banda Aceh - nur jannah; Intan Safiah; Mislinawati Mislinawati (Universitas Syiah Kuala, 2023)
This study aims to compare student learning outcomes using online learning models and offline learning models in science learning. This research is a comparative study with 2 samples. The population of this study was 158 grade 5 students at SDN 24 Banda Aceh, taking a sample of 64 students from the two available classes, namely VA and VB classes (online class and offline class) using a random sample technique from a total of four available classes. Data collection was carried out by administering a test instrument containing 10 choice questions (Post test). This test was conducted to see if there were differences in students' abilities between the online and offline groups. The researcher used a non-parametric statistical test data analysis technique, namely the Mann-Whitney test. From the calculation results of student learning outcomes data obtained a Z value of -2.112. This means that the cumulative probability value is -2.112 ˂ ∝ (0.05), then H0 is rejected, H1 is accepted, and a significant value (sig) is found, amounting to 0.035 ˂ 0.05. In this case, it means that there is a significant difference between student learning outcomes with the Online and Offline learning models in class V SD Negeri 24 Banda Aceh.